Analisis Faktor-Faktor yang Mempengaruhi Return Saham (Studi Kasus Pada Perusahaan Manufaktur Sektor Food and Beverages yang Terdaftar di BEI Periode 2013-2018) - Anni Lutfiani; Yanto Yanto (Accounting Study Program, Faculty of Economics and Business, 2020)
Opportunities for investment in food and beverage companies are very promising, because seen from sales turnover, food and beverage companies always experience an increase, of course this is very attractive for investors to invest their capital. The purpose of this study is to determine the effect of ROA, ROE, NPM, EPS, PER and DER on Manufacturing Companies in the Food and Beverages sector on the Indonesia Stock Exchange. The type of research used in this research is quantitative data. The dependent variable in this research is Stock Return. The independent variables in this study are: Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER). The population taken in this study was obtained from manufacturing companies in the food and beverages sector listed on the Indonesia Stock Exchange starting from 2013 to 2018 with a total of 29 companies. The results showed that the independent variables, namely ROA, ROE, NPM, EPS, PER and DER simultaneously affected the dependent variable of stock returns. This means that if the variables ROA, ROE, NPM, EPS, PER and DER if there is an increase or decrease, it will have an impact on increasing and decreasing stock returns listed on the Indonesia Stock Exchange in 2013 - 2016.